Strategi Pengelolaan Lingkungan Hidup di Sekolah: Praktik Baik Sekolah Adiwiyata - Mansir, Mirdan Ali Sabdillah; Nurfaidah, Sitti; La Fua, Jumarddin; Machmud, Hadi (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This article aims to identify the strategies of environmental management at an Adiwiyata school in South East Sulawesi, Indonesia. Data in this case study was gathered through interview, observation, and artefacts. Data analysis indicates that the school has its own strategy in gaining the status of Adiwiyata school. The school designed short, middle, and long-term plan for the implementation of participative-based activity for school environmental management. The best practices at school include programs such as Friday in faith, Saturday cleaning, self-development, extracurricular and innovative work for students in terms of educational management. The school also invited parents and companies to get involved in participative-teaching program dealing with innovative activities and entrepreneurship. This study suggests schools to implement best practice-based strategy by encouraging active participation of both school community and stakeholders in school environmental management.